The Role of Digital Technologies in the Transformation of Regional Models of Households’ Financial Behavior in the Conditions of the National Innovative Economy Development - Zhavoronok, А.; Popelo, O.; Shchur, R.; Ostrovska, N.; Kordzaia, N. (Ingénierie des Systèmes d’Information, 2022)
Households play one of the key roles in the development of the financial system of any country and the national economy in general. It is the understanding of the behavior of these economic entities in the market of financial services that makes it possible to predict the development of such a market, to understand the mechanisms of the emergence of dissipative processes in the interaction of households and financial institutions, which can form crisis phenomena in the development of such a system and restrain the innovative development of the national economy. This determines the importance and relevance of further research in this direction. Within the article, the impact of modern digital technologies on the development of financial services, in particular financial behavior of households, in the conditions of the formation and active development of the innovative economy is considered. Significant attention is paid to the specification of the methodology for determining the impact of the digitization index and the index of the model transformation of financial behavior of households. It is established that the outlined models are specific and different between various regions in any country. That is why the above method of calculation was used on the example of Ukraine. As a result, information was obtained on the digitalization index, and the transformation index of the financial behavior model of households in twenty-four regions of Ukraine. Based on the use of econometric analysis, algebraic equations of the dependence of the transformation index of the model of financial behavior of households on the digital technologies development in each of the outlined regions were determined.
Keywords: innovative economy, national economy, financial behavior of households, digitalization, digital technologies, regional model of financial behavior